2021
DOI: 10.1080/03007995.2021.1932446
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of cariprazine on function in patients with bipolar depression: a  post hoc analysis of a randomized controlled trial

Abstract: Introduction: Individuals with bipolar depression often experience functional impairment that interferes with recovery. These analyses examined the effects of cariprazine on functional outcomes in patients with bipolar I disorder. Methods: Prespecified analyses of data from a randomized, double-blind, placebo-controlled pivotal trial of cariprazine in bipolar I depression (NCT01396447) evaluated mean changes from baseline to week 8 in Functional Assessment Short Test (FAST) total score. Post hoc analyses with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Moreover, CAR is the only antipsychotic with proven superiority over another antipsychotic in the treatment of predominant negative symptoms, including anhedonia, avolition-apathy, and alogia (28). Furthermore, there are post-hoc analyses demonstrating improvement of cognitive dysfunction in different psychiatric disorders after CAR treatment (29)(30)(31)(32). indications: mitochondrial encephalomyopathy and lactic acidosis (MELAS syndrome) due to the mutation m.A3243G where the predominantly negative symptoms and cognitive dysfunction improved (33); substance use disorder (e.g., cocaine, alcohol, methamphetamine) (34,35); obsessive-compulsive disorder as add-on therapy (36) and borderline personality disorder (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CAR is the only antipsychotic with proven superiority over another antipsychotic in the treatment of predominant negative symptoms, including anhedonia, avolition-apathy, and alogia (28). Furthermore, there are post-hoc analyses demonstrating improvement of cognitive dysfunction in different psychiatric disorders after CAR treatment (29)(30)(31)(32). indications: mitochondrial encephalomyopathy and lactic acidosis (MELAS syndrome) due to the mutation m.A3243G where the predominantly negative symptoms and cognitive dysfunction improved (33); substance use disorder (e.g., cocaine, alcohol, methamphetamine) (34,35); obsessive-compulsive disorder as add-on therapy (36) and borderline personality disorder (37).…”
Section: Discussionmentioning
confidence: 99%
“…Patients have severe social and occupational dysfunctions, difficulty attending to everyday tasks due to clinical symptoms (especially negative, affective and cognitive) or comorbid conditions, which have detrimental effects on their quality of life—yet, it remains a large unmet need ( 81 ). Furthermore, its evaluation is not standardized, as there is no consensus definition of psychosocial functioning ( 82 ). This was reflected in the presented cases as well: 10 patients reported reduced psychosocial functioning for which cariprazine treatment was initiated.…”
Section: Discussionmentioning
confidence: 99%
“…Both cariprazine doses were safe, well tolerated, and effective in decreasing depressive symptoms [349]. Although a singular dosage recommendation has not been standardized for cariprazine yet, the results of these studies indicate its efficacy in certain cases of BD [346][347][348][349].…”
Section: Cariprazinementioning
confidence: 94%
“…Some research data have indicated that both low and high doses of cariprazine are effective and well tolerated as a drug treatment for mania, depression, and psychosis [343][344][345]. RCTs of BD-I patients in manic and mixed episodes found the greatest treatment benefit when cariprazine was provided in the range of 3 to 12 mg [346,347]. Placebo-controlled studies of bipolar depression have indicated that 1.5 to 3 mg/d of cariprazine monotherapy is a competent treatment for acute depression in BD [346].…”
Section: Cariprazinementioning
confidence: 99%